Literature Review: Effect of Brisk Walking on Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus - Sugiyarto, Sugiyarto; Sumardino, Sumardino; Yusran P., A. Dian Miranda (Basic and Applied Nursing Research Journal, 2022)
Diabetes is a chronic disease when the pancreas cannot produce enough insulin. Therefore, it takes a good way for sufferers to go through the entire process of diabetes treatment and care. Physical activity, such as brisk walking, has benefited people with diabetes and pre-diabetes. This activity has been shown to increase insulin sensitivity and reduce belly fat. Literature review aims to analyze the application of brisk walking to blood sugar levels in patients with type II diabetes mellitus over the past five years. Methods analysis of articles related to brisk walking in lowering blood sugar levels in patients with type II diabetes mellitus through data obtained from Google Scholar, EBSCO, and PubMed empirical studies in the last five years, as many as eight journals under the inclusion criteria set by the author. An analysis showed that brisk walking could reduce blood sugar levels in patients with type II diabetes mellitus. Based on the results of these eight journals, almost all journals have significant impacts that brisk walking affects blood sugar levels in patients with type II diabetes mellitus